$s$-$(τ_1,τ_2)$-continuity for multifunctions (European Journal of Pure and Applied Mathematics, 2025)
This paper deals with the concepts of upper $s$-$(τ_1,τ_2)$-continuous multifunctions and lower $s$-$(τ_1,τ_2)$-continuous multifunctions. Moreover, several characterizations and some properties concerning upper $s$-$(τ_1,τ_2)$-continuous multifunctions and lower $s$-$(τ_1,τ_2)$-continuous multifunctions are investigated.
Keywords: upper $s$-$(τ_1,τ_2)$-continuous multifunction; lower $s$-$(τ_1,τ_2)$-continuous multifunction